2016
DOI: 10.1093/brain/aww230
|View full text |Cite
|
Sign up to set email alerts
|

Like prions: the propagation of aggregated tau and α-synuclein in neurodegeneration

Abstract: The abnormal aggregation of a small number of known proteins underlies the most common human neurodegenerative diseases. In tauopathies and synucleinopathies, the normally soluble intracellular proteins tau and α-synuclein become insoluble and filamentous. In recent years, non-cell autonomous mechanisms of aggregate formation have come to the fore, suggesting that nucleation-dependent aggregation may occur in a localized fashion in human tauopathies and synucleinopathies, followed by seed-dependent propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
231
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(235 citation statements)
references
References 123 publications
1
231
0
3
Order By: Relevance
“…These studies were performed in the context of mounting evidence that points to prionlike transmission involving intercellular seeding as an important mechanism for the spread of tauopathy (4,(25)(26)(27) 55), with far reaching mechanistic and therapeutic implications. Seeding properties of many FTDP-17 mutants had yet to be examined, and current cultured cell tau seeding models tend to utilize either mutated truncated repeat domain (RD) tau (29,44,47), which can intrinsically aggregate in these models (56, 57), or full-length tau mutants at the P301 site (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were performed in the context of mounting evidence that points to prionlike transmission involving intercellular seeding as an important mechanism for the spread of tauopathy (4,(25)(26)(27) 55), with far reaching mechanistic and therapeutic implications. Seeding properties of many FTDP-17 mutants had yet to be examined, and current cultured cell tau seeding models tend to utilize either mutated truncated repeat domain (RD) tau (29,44,47), which can intrinsically aggregate in these models (56, 57), or full-length tau mutants at the P301 site (30).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic mutants at the P301 site (P301L, P301S, and P301T) and to a lesser extent at the S320 site (S320F) showed marked aggregation when cells were treated with exogenous pre-formed fibrillar tau seeds, while WT and the remaining FTDP-17 associated mutant tau displayed relatively limited to no aggregation, consistent with, and expanding upon, previous direct comparisons (30, 54). Furthermore, studies of other FTDP-17 mutations around the PHF6 site of tau as well as additional artificial mutants near this site or at other proline residues in the three other PGGG motifs within tau further demonstrated the unique properties of the P301 residue and mutants thereof in regulating seeding induced tau aggregation.These studies were performed in the context of mounting evidence that points to prionlike transmission involving intercellular seeding as an important mechanism for the spread of tauopathy (4,(25)(26)(27) 55), with far reaching mechanistic and therapeutic implications. Seeding properties of many FTDP-17 mutants had yet to be examined, and current cultured cell tau seeding models tend to utilize either mutated truncated repeat domain (RD) tau (29,44,47), which can intrinsically aggregate in these models (56, 57), or full-length tau mutants at the P301 site (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that the injection of tau inclusions into animal brains induces neurons to form intracellular inclusions at the injection sites, and their spreading to distant brain regions connected by neural network [13,14]. The concept of different 'strains' of tau aggregates is consolidated by animal studies demonstrating that the intracerebral injection of brain homogenates from humans with pathologically confirmed PSP, CBD and AGD produced distinct lesions in mouse brains similar to those of the respective human tauopathies [13].…”
Section: Propagation and Strainsmentioning
confidence: 99%
“…α ‐Synuclein, another aberrant protein that is present as insoluble cytoplasmic aggregates in neurodegenerative brain disorders also abnormally accumulates in IBM muscle fibers 211, 212, 213, 214, 215. Expression and toxicity of the small protein is increased under conditions of oxidative stress but is negatively regulated by the activity of heat shock proteins 216, 217, 218.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%